1986
DOI: 10.1017/s0022215100100052
|View full text |Cite
|
Sign up to set email alerts
|

The variability of fixation suppression of caloric-induced nystagmus

Abstract: Twelve normal adults were evaluated to determine their capacity to suppress caloric-induced nystagmus by visual fixation. Fixation suppression (FS) was assessed four times during the routine Fitzgerald-Hallpike caloric procedure. The results were characterized by large inter-subject as well as intra-subject variability. It is cautioned that diagnostic categories should not be inferred on the basis of absolute numeric values of FS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…This test method does have some limitations and should not be over-estimated. Several studies on visual fixation suppression in healthy control subjects have shown a high inter- and intra-individual variability of measurement results 30 . In our patients, the specificity of this test as an indicator for post-operative vertigo was only moderate.…”
contrasting
confidence: 44%
“…This test method does have some limitations and should not be over-estimated. Several studies on visual fixation suppression in healthy control subjects have shown a high inter- and intra-individual variability of measurement results 30 . In our patients, the specificity of this test as an indicator for post-operative vertigo was only moderate.…”
contrasting
confidence: 44%
“…A high variability was also reported for the fixation suppression index of caloric-induced nystagmus. 15 One potential problem with OFI scores is the problem of dividing values through zero or values close to zero explaining this variability. OFI scores are derived from a normalization procedure and represent a relative proportion of nystagmus suppression.…”
Section: Discussionmentioning
confidence: 99%